Navigating the maze of land abandonment: a tripartite evolutionary game and system dynamics approach to optimize governance strategies - Liao, Feng; Zheng, Yangyang; Yang, Di (Frontiers in Environmental Science, 2025)
IntroductionAddressing the issue of land abandonment in rural areas is a critical strategy for ensuring national food security and promoting high-quality agricultural and rural development.MethodsBased on the assumption of bounded rationality, this paper constructs an evolutionary game model involving three key stakeholders: farmers, village collectives, and local governments. By integrating system dynamics, we simulate and analyze the behavioral strategies of participants, examining the mechanisms of government regulation. Additionally, we explore the moderating role of agricultural social services and further investigate the impact of incentive and penalty measures.Results(1) under specific constraints, the system evolves toward the optimal equilibrium (1,1,1); (2) government policies influence the strategic choices of farmers and village collectives, with excessively high or low incentive and penalty measures proving ineffective in mitigating land abandonment; (3) compared to incentives, penalty measures exhibit a more substantial impact on addressing land abandonment; (4) enhancing agricultural social services can strengthen the effectiveness of incentive and penalty policies.DiscussionBased on these results, the paper offers policy recommendations from four perspectives: regulatory reform, the integration of incentives and penalties, flexible subsidies, and enhanced collaboration among key stakeholders, thereby providing both theoretical insights and practical guidance for addressing land abandonment.